Promoting a mixed-design model of scientific creativity through digital storytelling-the CCQ model for creativity - Zacharoula Smyrnaiou; Eleni Georgakopoulou; Sofoklis Sotiriou (SpringerOpen, 2020)
Abstract Background This study presents the development of three research tools of scientific creativity. Our aim is to evaluate the development of student creativity while students write digital stories. Three models are linked to create a new model, called Creative, Cognitive, Qualitative Model for Creativity (CCQ tool). Our research tool examines how creativity can be standardized, first by researchers' views and then by teachers and students' creative products. The first tool is based on two existing tools; the Scientific Creativity Structure Model (SCSM) and the TTCT Figural Subscales, and on new characteristics, the effective learning environments, as we have developed them in the CREATIONS Program. We have tried to expand this tool by combining its key elements to the theoretical framework of creativity, as we have approached it in the CREATIONS and the STORIES Programs. The second tool "Students' Creativity Evaluation Model" is a new tool that derives from empirical data and Grounded Theory methods. It examines the expected, original, and innovative ways of students' thinking. The third tool "Experts' Creativity Evaluation Model" allows us to examine the role of experts thinking on writing a story. It aims at tracking experts' model of thinking and is viewed in comparison to the students' creative model of thinking. We create a qualitative tool as we believe that a qualitative method delves deeper into students' internal mechanisms of creativity. Results Twelve students' stories from classrooms of different countries which participate to STORIES Program are analyzed indicatively by two independent researchers. The results seem to indicate that digital storytelling increases scientific creativity among students. Conclusions The main difference between expert and students' approaches is that experts' stories follow an up to bottom approach, while it is the opposite for students' creative process. It has to be mentioned that almost all of the stories combined science with creative thinking. Students transformed their personal values into stories; therefore, this creative procedure was influenced by social, cultural, and ethnographical characteristics. The contribution of our research is that it offers a research tool that not only measures creativity but also studies the cognitive mechanisms involved in creative thinking.